The synergistic bactericidal effects of bacteriocin and pressurization against E.coli O157:H7 in raw milk: Najim Hadi Najim@ and Namariq Ahmed Daher - Najim, Najim Hadi (The Iraqi Journal of Veterinary Medicine, 2014)
Colonies of E.coli O157:H7 were isolated from 35 raw milk sample and their identification were confirmed based on biochemical reactions and both cultural and serological characteristics. Presumptive E.coli O157:H7 isolates obtained by selective plating on both CT-SMAC and Chromogenic agars were further tested serologically for the presence of both O157 and H7 antigenes using the commercial available latex agglutination test kit. The unhygienic practices in the production of milk in Al-Thahab Al- Abiedh , Abu-Graib, Al-Zedan and Khan Dharie were reflected on the highest significant (p<0.01)prevalence level of contamination with E.coli O157:H7 that appeared to be 80%, 80%, 60% and60% respectively. Homogenization pressure of 1000 psi and 2000 psi for five passes had significantly (p<0.05) influenced the inactivation degree of E.coli O157:H7 in both whole milk and nutrient broth. Milk homogenized at a pressure level of 3000 psi for three passes and 4000 psi for two passes resulted in a further increase of the antimicrobial effectiveness and produced an additional significant (p<0.05) reduction of E.coli O157:H7. Complete elimination (inactivation) of viable E.coli O157:H7 was achieved when cultured whole milk was homogenized at pressure level of 5000 psi for a single pass. Agar well diffusion bioassay was used for the evaluation of antimicrobial activity of the crude bacteriocin produced by L.acidophilus LA-K against E.coli O157:H7. Enterohaemorrhagic E.coli O157:H7 expressed its resistance to the crude bacteriocin since it did not show any inhibition zone around each well treated with bacteriocin. The average diameters of the inhibition zones of crude bacteriocin against stressed E.coli O157:H7 by pressurization at 4000 psi, 3000 psi, 2000 psi and 1000 psi were 14 mm, 12mm, 10mm and 8mm respectively. The homogenization pressure level (moderate or high) had significantly (p<0.05) influenced the inactivation degree of the crude bacteriocin against the stressed E.coli O157:H7 by pressurization. Quantitative measurement of crude bacteriocin antimicrobial activity was determined by using photometric or turbidometric method. The results revealed that no growth of stressed E.coli O157:H7 with no visible turbidity in the nutrient broth with bacteriocin that diluted to 1/2, 1/4 and 1/8 were observed. Bacteriocin that diluted to 1/8 which resulted in no visible turbidity after overnight of incubation at 37C° and gave an optical density reading of 1.448.